Can Literature „speak culinary”? On Example of Categories of Elderly and Youth - Wiśniewska-Grabarczyk, Anna Ż. M. (Starość i młodość w literaturze i kulturze, 2016)
In this paper I examine how culinary scenes correspond with categories of elderly and youth. TextsI analyse differ in terms and the amount of culinary aspects — from simple enumeration of side andmain dishes to more detailed culinary scenes which are often remembered by the readers. The author ofthis paper is going to examine the ritual of tea brewing as performed by nubiles which is characteristicfor the 19th century literature. The most important is to reveral causes and consequences of this ritual.In the second part of the paper there will be analysed socialist-realist novel, which depicts old and youngpeople engaged in the act of eating. I debate whether the elderly and the youth are depicted similarly inthe culinary context. Additionally, I devote some attention to gender differences.